Solar Powered Green Campus: A Simulation Study - Baitule, Akshay Suhas; Sudhakar, K. (Oxford University Press, 2017)
Large-scale deployment of the renewable energy system in India is required to achieve a target of 175 GW of green electricity by 2022. Higher educational institutes with a lot of free areas can play a vital role in reducing the conventional energy consumption and carbon footprint. The main aim of this paper is to locate and analyze the feasibility of developing 100% solar PV based academic campus at MANIT – Bhopal, India. Annual electricity consumption of MANIT, Bhopal is analyzed and accordingly 5 MW capacity solar PV based captive plant is proposed. Free open space area of the campus including rooftop area is inspected through geographical coordinates utilizing the NASA surface meteorology data and Google SketchUp. The performance of the proposed solar campus is analyzed using PVSyst and Solar Advisory Model (SAM) software. The proposed plant at MANIT campus can generate around 8000 MWh per annum of electricity to meet the 100% energy requirements of the campus with the annual reduction of 73 318.0 tonnes of carbon footprint. Development and promotion of such sustainable green concepts will be a significant step towards transforming the academic campus into an energy efficient and environmentally sustainable community.